Pilot Symbol Based Channel Estimation and Capacity Evaluation in FBMC and OFDM - Kamislioglu, Bircan; Akbal, Ayhan (Ieee, 2017)
This paper presents pilot symbol aided channel estimation in Filter Bank Multicarrier (FBMC). FBMC has been employed widespread in communication applications because of its good spectral behaviors. Unlike Orthogonal Frequency Division Multiplexing, FBMC structure avoids imaginary interference. So that auxiliary symbols are employed and decrease peak to power ratio and improve achievable capacity. OFDM and FBMC are compared about achievable of channel estimation with pilot symbols. The achievable capacity is increased with linear precoding by interference cancellation. Using two or three auxiliary pilot symbols instead of one is purposed and achievable capacity via Signal to Noise Ratio (SNR) is compared. OFDM and FBMC with coding and auxiliary symbols are discussed about capacity and numerical results are realized in Matlab.
2017 International Artificial Intelligence and Data Processing Symposium (IDAP) -- SEP 16-17, 2017 -- Malatya, TURKEY
Keywords: FBMC; channel estimation; OFDM; pilot symbols